Examining the Intersection Performance of the Post-Disaster Permanent Housing Assistance Impact: A Study of the Trip Generation/Attraction in Palu City. Issue 1 (1st November 2022) - Bahar, T; Tahir, A; Mashuri,; Isratun,
Abstract: The government provides housing assistance for victims of the disaster that hit Palu City in Central Sulawesi Province. Most of the housing assistance is in Tondo Village, which is referred to as Tondo's permanent housing (Huntap Tondo). Currently, the TPH has become a source of traffic movement, especially for the Tondo ring road intersection - Street Untad 1. Thus, this study aims to examine the impact of the Tondo permanent residential trip generation/attraction on performing the intersection. The method of this research is to calculate the trip generation/attraction that occurs because of the existence of the Tondo's permanent housing and calculate the performance of the Tondo ring road intersection - Street Untad 1 using the Indonesian Highway Capacity Manual (MKJI) in 1997. This study reveals the value of the trip generation/attraction rate that occurs in the the Tondo's permanent housing is 0.175 pcu/unit with a total trip generation/attraction of 549 pcu/hr. Meanwhile, performing the ring road intersection Tondo - street Untad 1 decreased the value of saturation by 0.45 to 0.64, and the delay value of 8.63 seconds/pcu to 10.52 seconds/pcu.